A survey analysis on abandoned housing projects in Malaysia. The house buyers’ perspectives - Haron, Razali; Abd. Razak, Dzuljastri; Jaiyeoba, Haruna Babatunde (Journal of Global Business and Social Entrepreneurship (GBSE), 2016)
The Ministry of Housing and Local Government’s regards abandoned housing projects as a highly serious problem. As of June 2015, Malaysia records 10,403 house buyers being affected from 15,206 abandoned housing units on 53 housing projects. This study, therefore looks into this matter through a survey analysis on 328 house buyers covering 11 states in Malaysia. Lack of enforcement of housing law and policy is detected as one of the main contributing factors of this problem and the house buyers are not adequately protected under the existing law and practices. The developers and the banks have taken advantage of the Sell Then Build (STB) system where associated risks were being transferred to the house buyers through progressive payments and the monthly instalments. The study provides insights to practitioners and policy makers on necessary improvements of the law and policy to protect house buyers’ interests and to avoid abandoned housing projects in Malaysia.